Students’ Perception of The Use of Mobile Learning on Rhythmic Gymnastics Learning at Senior High School Level - Oktariyana, Oktariyana; Sukmawati, Noviria; Fauzi, Diah; Febrian, Mario (Universitas Negeri Semarang, 2019)
This research is motivated by advances and technology that are increasingly developing in all fields, one of which is education, which encourages physical education teachers in delivering rhythmic gymnastics material to innovate in the use of a set of learning media based on mobile learning. This study aims to determine students 'perceptions of the use of mobile learning as seen from 1) Students' understanding of mobile learning in rhythmic gymnastics learning; 2) The benefits of mobile-learning in rhythmic gymnastics learning; 3) Readiness of students in the use of mobile learning. This research is descriptive quantitative research. The results of this study indicate that 78.75% of students understand mobile learning, 81.83% of students know the benefits of mobile learning and 79.08% of students declare readiness for the use of mobile learning. The results of these studies are expected to be used as a reference in the application of mobile learning not only on rhythmic gymnastics learning material. But it can be applied to other materials.Â Â